2022
DOI: 10.14569/ijacsa.2022.01312101
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Detection from Text and Sentiment Analysis of Ukraine Russia War using Machine Learning Technique

Abstract: In the human body, emotion plays a critical function. Emotion is the most significant subject in human-machine interaction. In economic contexts, emotion detection is equally essential. Emotion detection is crucial in making any decision. Several approaches were explored to determine emotion in text. People increasingly use social media to share their views, and researchers strive to decipher emotions from this medium. There has been some work on emotion detection from the text and sentiment analysis. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The combination mechanisms include max voting, averaging, weighted averaging, etc. While individual baseline classifiers offer low accuracy and tend to overfit, an ensemble of those base classifiers can reduce overfitting and improve the accuracy [192]. In addition, ensemble learning offers good generalization and robustness [193].…”
Section: (B) Ensemble Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination mechanisms include max voting, averaging, weighted averaging, etc. While individual baseline classifiers offer low accuracy and tend to overfit, an ensemble of those base classifiers can reduce overfitting and improve the accuracy [192]. In addition, ensemble learning offers good generalization and robustness [193].…”
Section: (B) Ensemble Learningmentioning
confidence: 99%
“…Maruf et. al [192] used the bagging and boosting ensemble model. Initially, they used the baseline classifier and found that the accuracy was low and overfitting occurred.…”
Section: (B) Ensemble Learningmentioning
confidence: 99%